CHINA’S ENERGY POLICY TOWARD CENTRAL ASIA AND THE IMPORTANCE OF KAZAKHSTAN - Furkan KÜÇÜK, Zeki (CENTRAL ASIA AND THE CAUCASUS, 2009)
oil has been a strategic commodity since the industrial revolution, and it is the most influential element in contemporary world political history. When we observe historically important events, we can see that oil somehow affects these events and creates their causes. Good examples of this are World War I and II, the Gulf Wars, and the Oil Crises. Oil, as the only resource of the developed and developing countries, is likely to continue shaping world political history in the near future. In this context, China has very interesting conditions. China has to overcome its energy hunger in order to continue its economic boom. However, China has an enormous population, which makes it very different from the other developing countries. In order to feed its 1.3 billion people and huge economy, China needs much more energy than other developing countries. The existing situation in China has many similarities to the Central Powers’ situation before World War I. The Central Powers completed their industrialization process later than other nations of the world; they could not gain control over the necessary raw materials and had to fight with the states that controlled these sources. China began its economic development in the 1970s, much later than the other important powers, and until 1993 it was self-sufficient in terms of energy. After that China began looking for energy resources elsewhere and started importing 60 percent of its oil from the Middle East, which is under the control of the U.S. The Caspian Region, which is one of the richest oil sources in the world, is under the control of Russia. So the oil valves crucial for China’s economic development are in the hands of other powers. This is why China is trying to find new energy resources, taking steps to diversify its energy sources, and making energy investments in Africa and South America. However, considering the size of its economy, it is almost impossible to feed the Chinese economy by means of these resources alone. This is why China wants to gain a stronger foothold in the Middle East and the Caspian Region. China completed its economic development and, just like the Central Powers before World War I, began looking for more energy in every part of the world. In this context, we need to know whether China will follow an aggressive policy like the Central Powers or whether it will feed its economy by compromising with other powers